(untitled) ("Conference on Universal Science Research 2023", 2024)
Phraseological unit is a combination of words that has a specific meaning that is not necessarily derived from the individual meanings of the words themselves. In the context of studies and finance, understanding phraseological units related to these fields is crucial for effective communication and comprehension. In studies, specific phraseological units may be used to convey complex ideas or concepts in a succinct manner. These units can include academic jargon, technical terms, or idiomatic expressions that are commonly used within a particular discipline. Familiarity with these phraseological units is essential for students and researchers to effectively engage with scholarly literature and contribute to academic discourse. In finance, the use of phraseological units is particularly prevalent due to the specialized nature of the field. Terms such as “bull market,” “liquidity ratio,” or “capital gains” are examples of phraseological units that carry distinct meanings within the context of finance. Understanding and using these units accurately is essential for professionals working in finance, as they form the basis for clear and precise communication in financial reporting, analysis, and decision-making. Overall, being aware of phraseological units related to studies and finance is crucial for effective communication and comprehension within these fields. Whether it involves understanding academic literature or engaging in financial transactions, mastery of these specialized language constructs is fundamental for success in both academia and professional practice.